Vegetable Selection and Storage: a New Food Concept - Pereira, S. G.; Chairuca, B.; Rossini, L.; Andrade, M.; Fenhane, S.; Caravela, S.; Laisse, W.; Yassin, Y.; Silva, B.; Chaves, B.; Mijares, D.; Tenreiro, L. -N.; et al. (Open Schools Journal for Open Science, 2020)
A problem of malnutrition has been identified in Mozambique, specifically in Ponta de Ouro Marine Reserve. The project embraces the selection, conservation and preparation of packages of dehydrated vegetables (Corn, cassava, beans, moringa and peanuts), that contain the widest range of nutrients possible, easy to produce and prepare: Xima1 enriched. Thereby, we hope to improve the cognitive, intellectual and motor development of children and the community in general. Xima is a ground corn flour that's turn into a sort of porridge. It is eaten all over sub-Saharan Africa.